2010
DOI: 10.1111/j.1365-3083.2010.02466.x
|View full text |Cite
|
Sign up to set email alerts
|

Small Islets are Essential for Successful Intraportal Transplantation in a Diabetes Mouse Model

Abstract: Optimization of islet transplantation protocols is necessary for improved success of treatment for type 1 diabetes. Here, we investigated whether the size of islets transplanted into the portal vein (PV) of the liver can affect engraftment in the early post‐transplantation in an experimental mouse model. Small (average diameter < 250 μm, group A) or large (average diameter > 250 μm, group B) islets (400 islet equivalents/recipient) purified from normal BALB/c mice were transplanted into syngenic recipients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…In contrast, islets exposed to KU-32 showed less cell death (Figure 1(b), right). Islets maintained in culture have an increasing percentage of cell death, as we and others have shown [16, 17, 19, 20]. Exposure to KU-32 halted the time-dependent increase in cell death.…”
Section: Resultssupporting
confidence: 55%
“…In contrast, islets exposed to KU-32 showed less cell death (Figure 1(b), right). Islets maintained in culture have an increasing percentage of cell death, as we and others have shown [16, 17, 19, 20]. Exposure to KU-32 halted the time-dependent increase in cell death.…”
Section: Resultssupporting
confidence: 55%
“…Smaller islets have been shown to have improved nutrient supply, with larger islets depleted of both oxygen and glucose at the core [34,35]. Smaller islets also exhibit improved insulin secretory function in vitro, exhibit a higher vascular density and function preferentially in transplant models [20][21][22][23][24]. Studies with human islets in vitro also reproduce some of these results; small human islets were shown to be less susceptible to hypoxia and had improved secretory function compared with large islets [15,36].…”
Section: Discussionmentioning
confidence: 84%
“…Indeed, a number of in vitro studies have shown that smaller islets have superior function compared to larger ones [20][21][22][23][24]. However, data confirming this in clinical studies are more limited.…”
Section: Introductionmentioning
confidence: 99%
“…Recent publications show that mouse smaller islets perform better than larger islets when exposed to hypoxia followed syngeneic transplantation under the kidney capsule. 4,5,12 The smaller islet diameter implies a shorter diffusion distance and thereby a more effective supply of oxygen and nutrients. Evidence that the COPAS is not detrimental for islet function and viability opens the opportunity of applying this technology for the sorting of thousands of islets of homogeneous size within a few hours-a task that is unfeasible by manual sorting.…”
Section: Discussionmentioning
confidence: 99%